Heat impact on total phenolic content and antioxidant activity of Malaysian Tualang and Kelulut honey (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
The effect of temperature at 50°C, 70°C and 100°C for up to 120 min on the content of phenolic compounds and antioxidant activity of Tualang honey and Kelulut honey was studied. Unheated honey samples for both varieties were used as control. The total phenolic content and antioxidant activity were examined using Folin-Ciocalteau and DPPH assays, respectively. Both honeys vary widely in the total phenolic content as well as antioxidant activity upon heating and time of heating. The total phenolic content in both honeys showed fluctuations at all temperatures throughout 120 min. In comparison to controls for both honeys, heating at 100°C for 10 min demonstrated a drop in total phenolic content in Tualang honey (13%) and Kelulut honey (29%), but the antioxidant activity increased 29% and 57% in Tualang and Kelulut honey, respectively. The study generates information on the characteristics of components in both honeys which react differently to heat and time of heating, therefore this will help the honey manufacturers or public to optimize the processing protocols and later to preserve the quality of honey.
Keywords: Heterotrigona itama; polyphenolics; temperature; DPPH